Acoustic analysis of Malay /r/ in connected speech: A preliminary study on tap and trill variants - Wan Aslynn, W. A.; Muhammad Roslan,; Nur Hanisah Tukiran, (Journal of Modern Languages, 2025)
Differences in regional dialects in the production of consonants and vowels can influence the pronunciation of Standard Malay. This study aims to acoustically characterise the pronunciation of the Malay phoneme /r/, a consonant known to exhibit phonetic variation. The data analysed in this study contained both tap [ɾ] and trill [r] realisations of /r/. A total of 74 tokens containing the /r/ sound were extracted from audio recordings of four Standard Malay-speaking participants. Based on acoustic analysis, it was found that the /r/ phoneme was consistently realised as either a tap or trill in initial and medial positions, while it was frequently omitted in word-final position. These findings have clinical relevance for speech-language pathology, particularly in differentiating between typical dialectal variation and disordered speech.